Electrical label-free sensing of cardiac troponin biomarker: fet-based integration with substrate-gate coupling - Mohamad Faris Mohamad Fathil (Institute of Nano Electronic Engineering, 2017)
The scopes of this research work are distributed into five parts. The scope of this research work starts with selectivity verification of MAb-cTnI as bio-receptor for the detection of cTnI biomarker. The MAb-cTnI is tested with two different cTn biomarkers, which are cTnI and cTnT at different range of protein concentration by using conventional ELISA.The second research scope is the ZnO-NPs thin film deposition as the channel between drain and source region on the biosensor. The available deposition techniques for thin film deposition are pulsed laser deposition, RF magneton sputtering, chemical vapour deposition, spray pyrolysis, electrodeposition, and sol-gel. This work utilized sol-gel and spin-coating techniques due to the straightforwardness, low cost, and highly controlled deposition of ZnO-NPs thin film. In this scope also, the surfaces of these thin films are characterized morphologically by using atomic force microscope (AFM) and field-emission scanning electron microscope (FESEM). The structural properties and crystalline phase of the thin film are characterized by using XRD while the electrical characterizations of the thin film are conducted by using semiconductor parametric analyzer (SPA).